Estrogen-Related Receptor γ Agonist DY131 Ameliorates Lipopolysaccharide-Induced Acute Liver Injury - Ma, Haoyang; Liu, Jiaye; Du, Yang; Zhang, Shengnan; Cao, Weidong; Jia, Zhanjun; Gong, Wei; Zhang, Aihua (Frontiers in Pharmacology, 2021)
Sepsis-associated liver dysfunction remains a challenge in clinical practice with high mortality and limited specific therapies. DY131 is a pharmacological agonist of the orphan receptor estrogen-related receptor (ERR) γ which plays a crucial role in regulating energy generation, oxidative metabolism, cell apoptosis, inflammatory responses, etc. However, its role in acute liver injury is unknown. In this study, we evaluated the effect of DY131 on lipopolysaccharide (LPS)-induced liver injury. Mice were pretreated with DY131 through intraperitoneal injection at a dose of 5 mg/kg/day for three days prior to LPS challenge (10 mg/kg). 24 hours later, they were anesthetized and sacrificed. Blood and liver tissues were collected for further studies. In a separate experiment, mice were treated with saline (vehicle) or DY131 for three days to evaluate the toxicity of DY131. We found that ERRγ was downregulated in the liver tissues from LPS-treated mice. Pretreatment with DY131 ameliorated LPS-induced liver injury as demonstrated by reduced liver enzyme release (ALT, AST and LDH), improved liver morphological damage, and attenuated oxidative stress, inflammation and apoptosis. Meanwhile, DY131 had no significant side effects on hepatic and renal functions in mice. Finally, transcriptomics analysis revealed that the dysregulated pathways associated with inflammation and metabolism were significantly reversed by DY131 in LPS-treated mice, providing more evidence in favor of the protective effect of DY131 against LPS-induced liver injury. Altogether, these findings highlighted the protective effect of DY131 on LPS-induced hepatotoxicity possibly via suppressing oxidative stress, inflammation, and apoptosis.